Complex treatment of vascular prostheses infections. Issue 27 (July 2018) - Andercou, Octavian; Marian, Dorin; Olteanu, Gabriel; Stancu, Bogdan; Cucuruz, Beatrix; Noppeney, Thomas
Abstract : Abstract: Infections after vascular reconstructions are very rare; however, when they occur, they are associated with a high risk of morbidity. In order to obtain the best results possible, the treatment needs to be initiated as early as possible, from the very first signs of infection, and it needs to be carried out in centers specializing in vascular surgery. The aim of the present study was to assess the incidence of infections in a single university center. This retrospective analysis over a 2-year period is based on the medical reports of hospitalized patients who were diagnosed with infection following revascularization. From 2013 to 2014, a number of 151 open reconstructive surgical procedures were performed. 15 patients suffered from infection (10%) of the vascular reconstruction. Of these patients, 40% have had an aorto-bifemoral bypass, 53%—a femoro-popliteal bypass, and 7% (n = 1)—an axillo-femoral bypass. According to the Samson classification, the patients were categorized as follows: group 2: 6 cases, group 3: 2 cases, group 4: 4 cases, and group 5: 3 cases. The most frequent bacteria found were methicillin-resistant Staphylococcus aureus (MRSA) (n = 6, 40%), followed by S aureus (n = 5, 33%). The treatment options were: application of antibiotics alone without any invasive treatment in 3 patients, local irrigation and debridement in 6 patients, complete explantation of the prosthesis with a new extra-anatomic bypass in 6 cases, and partial excision of the prosthesis, which was replaced and covered with muscle flap, in 3 cases. The amputation rate in our study was 18%, which corresponds to the rates published in the literature. The treatment of infections in vascular surgery needs to be complex and adapted to each individual patient, because infections being in a permanent dynamic state. The treatment needs to be performed in specialized centers that have large experience in vascular surgery, in order for the patient to have the best chances of survival and protection from amputation.